The impact of explicit instruction concerning grammar and lexical-related matters in the Spanish heritage language classroom: searching for an effective way to teach aspectual distinction and semantic properties of homophones and homographs - Gonzalez, Alejandra (Kansas State University, 2019)
Heritage language learners (hereafter HLLs), bilinguals who are exposed to Spanish from an early age in home contexts, possess varying proficiency levels of the minority language (Valdés, 1997). This can be explained by various factors concerning exposure, such as the quality (minoritized variety of Spanish) and the quantity of input (limited to casual contexts) (Beaudrie et al., 2015; Potowski, 2018; Rothman, 2007). More often than not, another determining aspect of proficiency fluctuation among this linguistic population is the limited access to formal instruction (Lynch & Potowski, 2014). Those fluent HLLs enrolled in Spanish classes often face unrealistic linguistic expectations (Beaudrie et al., 2015). To better prepare language instructors to teach this population and build on HLL’s strengths, further research on the effect of teaching practices in the heritage language classroom is crucial. Thus, this study aims to evaluate the impact of explicit instruction on a) HLLs’ grammatical judgment of the aspectual distinction (i.e., preterit and imperfect) and b) HLLs’ recognition of the semantic difference in homophones (e.g., tuvo vs tubo) and homographs (e.g., hacia vs hacía) distinguished solely by the addition of diacritic accent marks (e.g., tu vs tú). The results of this study suggest that explicit grammar instruction has an overall negative impact on grammar-related matters. Nevertheless, direct instruction on the semantic contrast between homophones through the selection and implementation of diacritic accent marks significantly facilitated the development of a wider lexical repertoire.
Keywords: Spanish heritage language learners; Explicit instruction; Aspectual distinction; Homophones; Homographs